Pengaruh Lingkungan Kerja dan Kepuasan Kerja terhadap Kinerja Pegawai RSU BMC Bireuen - Ariska, Emalia; Mulyadi, Mulyadi; Zalikha, Zalikha; Yusuf, M (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to determine the influence of the work environment and job satisfaction on the performance of RSU BMC Bireuen employees. The sample in this study was 75 employees at RSU BMC Bireuen. The method used in this research is a quantitative descriptive method. The research results stated that the work environment and job satisfaction influenced the performance of Labuhanbatu District Health Service employees. The results of this research state that the work environment variable has a positive and significant effect on employee performance with a t-statistic path coefficient value of 6,934 > 1,658 and has a significant value of 0,000 < 0.05 and the Job Satisfaction variable has a significant effect on the Performance of Labuhanbatu Regency Health Service Employees. This is clear from the t-statistical path coefficient value of 1,893 > 1,658 and has a significant value of 0.058 < 0.05. Thus the results of testing the second hypothesis in the research were rejected.